PENGARUH FITUR GRABFOOD, HARGA, DAN PROMOSI TERHADAP MINAT BELI KONSUMEN PADA PENGGUNA APLIKASI GRAB DI KOTA MEDAN - Auliya, Aina (Jurnal Mahkota Bisnis (Makbis), 2023)
This research is a scientific work carried out with the aim of knowing the effect of grabfood features, prices and promotions on consumer buying interest in grab application users in the city of Medan. In this study using quantitative descriptive methods with data collection techniques carried out by distributing questionnaires, interviews, and observations. Respondents used in this study are consumers who have used the Grabfood delivery service application. The number of respondents or samples in this study amounted to 100 people, with = 0.5. From the results of data processing and statistical tests of research, it is found that the results of this study partially prove the research variables, namely grabfood features, prices and promotions have a positive and significant effect on consumer buying interest in grab application users in the city of Medan. Furthermore, simultaneously or jointly give the results that the grabfood feature, price and promotion have a positive and significant effect on consumer buying interest in Grab application users in the city of Medan.